BUDAYA GENDER DALAM MASYARAKAT PERSPEKTIF TEMPORAL EKOLOGI DAN SOSIAL EKONOMI - Mustam, Amiruddin (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2017)
This paper discusses Indonesian women since time immemorial has been active in various economic activities to support the household economy. In the current information age the gait of Indonesian women in careers is getting more advanced and has occupied various business sectors. Besides it also appears as a comrade is a general perception that tends to degrade women's dignity, such as violence, and deviations from the normative culture of the Indonesian nation. Therefore, to maximize the potential of women in social aspects, it is necessary to create a new social order for women through empowering women resources that are crippled in the formation of three attitudes: attitude and behavior towards God's, attitudes and behavior towards self, and attitudes and behavior toward values -Community values.